Taking Form, Making Worlds: Cartonera Publishers in Latin America. - Zentella, Yoly (Journal of Global South Studies)
The article reviews "Taking Form, Making Worlds: Cartonera Publishers in Latin America," which examines grassroots self-publishing movements in Latin America, particularly focusing on the creation of books from recycled cardboard. The authors, Lucy Bell, Alex Ungprateeb Flynn, and Patrick O’Hare, explore the collaborative efforts of diverse community members, including artists and Indigenous groups, in the cartonera publishing phenomenon that emerged in response to socio-political challenges. The book, which won the 2023 Latin American Studies Association Best Book in Visual Culture Studies award, is structured into six chapters that detail the histories, methods, texts, encounters, workshops, and exhibitions related to cartonera publishing, emphasizing its role as a form of resistance and community empowerment.